Use of rituximab in connective tissue disease-associated interstitial lung disease: a narrative review - Xu, Chenhao; Xu, Zewei; Ren, Jin (Frontiers in Medicine, 2025)
This narrative review examines the therapeutic potential of rituximab, a monoclonal antibody targeting CD20 antigens, for treating connective tissue disease-associated interstitial lung disease. It outlines how rituximab offers a promising therapeutic option, particularly for patients who exhibit limited responses to standard therapies like glucocorticoids and immunosuppressive agents. Rituximab’s mechanism of action, involving B lymphocyte depletion, contributes to attenuated inflammation and may slow pulmonary fibrosis progression. The article synthesizes findings from studies assessing rituximab’s effects on lung function, clinical outcomes, and safety across distinct subtypes of connective tissue disease. It also discusses differential treatment responses based on disease characteristics and pathological subtypes, noting evidence that rituximab may be more effective as an initial treatment in some cases, though further investigation into long-term efficacy remains essential. Despite some associated risks, particularly infections, rituximab generally presents a favorable safety profile compared with conventional immunosuppressive therapies. Future research directions include optimizing dosing protocols, treatment intervals, and patient selection criteria, with emphasis on conducting rigorous, long-term randomized controlled trials to more definitively establish rituximab’s role in managing interstitial lung disease in the context of connective tissue diseases.